The impact of Design Thinking on innovativeness of an organization and personal creativity of its employees - Modrzejewska, Dagmara (Wpływ Design Thinking na innowacyjność własną i organizacji, 2020)
The article present the impact of Design Thinking on current management theory and practice in the area of innovations in organization, personal and organisational innovativeness and their impact on organisational culture. The use of Design Thinking method to build, maintain, manage, improve and develop an organisation in the area of its innovation and the employees’ own creativity, offers the opportunity to enrich the existing scientific research by broadening the knowledge in this area. Design Thinking is also a holistic approach to cooperation with the organization’s stakeholders. Skilful listening to feedback (comments and what they have to say about products/services) and using this information as a contribution to further development and improvement of both the organisation’s product offer, and one’s expertise (know-how), is the key to success today
Informatyka Ekonomiczna = Business Informatics, 2020, Nr 2 (56), s. 43-51
Keywords: design thinking; personal innovativeness; organizational innovations; creative method; iterative process; innovations; innowacyjność własna; innowacyjność organizacji; twórcza metoda; proces iteracyjny; innowacje